Protein kinase D3 promotes neutrophil migration during viral infection. Issue 2 (24th November 2022) - Veazey, Janelle M; Wong, Gordon S; Eliseeva, Sophia I; Smyth, Timothy R; Chapman, Timothy J; Lim, Kihong; Kim, Minsoo; Georas, Steve N
Abstract: Protein kinase D (PKD) is a serine/threonine kinase family with three isoforms (PKD1–3) that are expressed in most cells and implicated in a wide array of signaling pathways, including cell growth, differentiation, transcription, secretion, polarization and actin turnover. Despite growing interest in PKD, relatively little is known about the role of PKD in immune responses. We recently published that inhibiting PKD limits proinflammatory cytokine secretion and leukocyte accumulation in mouse models of viral infection, and that PKD3 is highly expressed in the murine lung and immune cell populations. Here we focus on the immune‐related phenotypes of PKD3 knockout mice. We report that PKD3 is necessary for maximal neutrophil accumulation in the lung following challenge with inhaled polyinosinic:polycytidylic acid, a double‐stranded RNA, as well as following influenza A virus infection . Using reciprocal bone marrow chimeras, we found that PKD3 is required in the hematopoietic compartment for optimal neutrophil migration to the lung. Ex vivo transwell and chemokinesis assays confirmed that PKD3 −/− neutrophils possess an intrinsic motility defect, partly because of reduced surface expression of CD18, which is critical for leukocyte migration. Finally, the peak of neutrophilia was significantly reduced in PKD3 −/− mice after lethal influenza A virus infection. Together, these results demonstrate that PKD3 has an essential, and nonredundant, role in promoting neutrophil recruitment to the lung. A better understanding of the isoform‐specific and cell type–specific activities of PKD has the potential to lead to novel therapeutics for respiratory illnesses. Abstract : In this study, we identified a novel role for protein kinase 3 (PKD3) in neutrophil migration. Using mouse models of respiratory viral infection, we found that fewer PKD3‐deficient neutrophils accumulated in the lung compared with wild‐type controls. PKD3‐deficient neutrophils were also defective in in vitro assays of both directional and nondirectional migration and exhibited lower levels of CD18 on the surface. Taken together, these data demonstrate that PKD3 inhibitors might limit neutrophil accumulation at sites of inflammation. This figure was created using BioRender.